2015
DOI: 10.1139/apnm-2015-0064
|View full text |Cite
|
Sign up to set email alerts
|

A kinematic and metabolic analysis of the first Lu of Tai Chi in experts and beginners

Abstract: The aim of this study was to compare movement kinematics, cocontraction times, and metabolic data in expert and nonexpert Tai Chi practitioners. Significant differences were observed for all kinematic parameters: experts moved smoothly (lower jerk) and with a lower frequency. No differences in metabolic and electromyography data were observed but for the breathing pattern (experts breathed slowly and deeply). Movement frequency and breathing pattern are thus the main features that distinguish expert and nonexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Of specific relevance to mind-body practices, some of the key features of posture and movement associated with improved mood that we identified in our literature review are principles typically emphasized in TCQ training. Some of these features, such as balanced muscular tone during static and dynamic activities (Forrest, 1997 ; Wolf et al, 1997 ; Gatts, 2008 ; Cho, 2014 ; Zorzi et al, 2015 ) and steadier gait dynamics (Manor et al, 2014 ; Wayne et al, 2015 ), have been objectively documented in a handful of TCQ studies. Many other features associated with improved mood, such as upright vs. slumped torso, minimized neck flexion, smooth vs. sharp movement rhythms, relaxed arm swings during weight shifting and gait, and soft facial expressions (e.g., relaxed jaw, soft eye gaze), have not been objectively measured, but are emphasized in training manuals (Lo et al, 1979 ; Wile, 1996 ; Wayne and Fuerst, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of specific relevance to mind-body practices, some of the key features of posture and movement associated with improved mood that we identified in our literature review are principles typically emphasized in TCQ training. Some of these features, such as balanced muscular tone during static and dynamic activities (Forrest, 1997 ; Wolf et al, 1997 ; Gatts, 2008 ; Cho, 2014 ; Zorzi et al, 2015 ) and steadier gait dynamics (Manor et al, 2014 ; Wayne et al, 2015 ), have been objectively documented in a handful of TCQ studies. Many other features associated with improved mood, such as upright vs. slumped torso, minimized neck flexion, smooth vs. sharp movement rhythms, relaxed arm swings during weight shifting and gait, and soft facial expressions (e.g., relaxed jaw, soft eye gaze), have not been objectively measured, but are emphasized in training manuals (Lo et al, 1979 ; Wile, 1996 ; Wayne and Fuerst, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of specific relevance to mind-body practices, some of the key features of posture and movement associated with improved mood that we identified in our literature review are principles typically emphasized in TCQ training. Some of these features, such as balanced muscular tone during static and dynamic activities (Forrest, 1997;Wolf et al, 1997;Gatts, 2008;Cho, 2014;Zorzi et al, 2015) and steadier gait dynamics (Manor et al, 2014;Wayne et al, 2015), have been objectively documented in a handful of TCQ studies. Many other features associated with improved mood, such as upright vs. slumped torso, minimized neck flexion, smooth vs. sharp movement rhythms, relaxed arm swings during weight shifting and gait, and soft facial expressions (e.g., relaxed jaw, soft eye gaze), have not been objectively measured, but are emphasized in training manuals (Lo et al, 1979;Wile, 1996;Wayne and Fuerst, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Rinaldi et al (2018) studied the Junzuki karate punch using a cut off frequency of 10 [Hz]. Tsai et al (2017) analyzed in kendo the Hiki Waza, using cut-off frequencies of 6 [Hz], while Zorzi et al (2015) reported in Tai Chi practitioners during the First Lu, the use of cut-off frequencies of 4 [Hz]. Conversely, the signal's root mean square (RMS) is often calculated with different window width parameters in combat sports as a measure of wave softening.…”
Section: Introductionmentioning
confidence: 99%